If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3 + 5(4x + 6) = 2x + -3 Reorder the terms: 3 + 5(6 + 4x) = 2x + -3 3 + (6 * 5 + 4x * 5) = 2x + -3 3 + (30 + 20x) = 2x + -3 Combine like terms: 3 + 30 = 33 33 + 20x = 2x + -3 Reorder the terms: 33 + 20x = -3 + 2x Solving 33 + 20x = -3 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 33 + 20x + -2x = -3 + 2x + -2x Combine like terms: 20x + -2x = 18x 33 + 18x = -3 + 2x + -2x Combine like terms: 2x + -2x = 0 33 + 18x = -3 + 0 33 + 18x = -3 Add '-33' to each side of the equation. 33 + -33 + 18x = -3 + -33 Combine like terms: 33 + -33 = 0 0 + 18x = -3 + -33 18x = -3 + -33 Combine like terms: -3 + -33 = -36 18x = -36 Divide each side by '18'. x = -2 Simplifying x = -2
| 6/7(y-2)-26/7=4 | | -3x+5+9x=11 | | -2(3-2x)=2(5-2x) | | x+4=-5x+4 | | 3x^2-15x=10 | | -5x+12+8x=3x+3 | | 5y-6=4y+4 | | 3x+30=5x | | D=k+p/2 | | 2/3(4x-7)=-3 | | 3k+2k=6+3k | | 2x-3-4x+5=10 | | 8x+33=3-2x | | 9-3c=36 | | (5/-9)(-2/7)(-3) | | 2x+2=4x-11 | | 60+c=-10 | | 6(2x+3)-3x=63 | | 7y*4.6= | | 20-5c=50 | | 3/4m=-2/3 | | 5/-9x-2/7x-3 | | -3x+7+2x=37 | | 2/3m=3/4 | | (x^2-4)(x^2-4)=-5 | | 3x+7+2x=37 | | 2x+3+2=-1 | | 2x=103+x | | -2(4x-5)=38 | | 10=25+.5x | | 11=5(n-9) | | 6(9x+18)=60 |